Outgassing from the OSIRIS-REx sample return capsule: characterization and mitigation. (January 2020) - Sandford, Scott A.; Bierhaus, Edward B.; Antreasian, Peter; Leonard, Jason; Materese, Christopher K.; May, Christian W.; Songer, Jarvis T.; Dworkin, Jason P.; Lauretta, Dante S.; Rizk, Bashar; ,
Abstract: The Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer (OSIRIS-REx) spacecraft launched on September 8, 2016, beginning a seven-year journey to return at least 60 g of asteroid material from (101955) Bennu to Earth. During the outbound cruise, Doppler tracking of the spacecraft observed a small but measurable acceleration when the sample return capsule (SRC) was first placed in sunlight. Subsequent analysis determined that outgassing from the SRC is the most likely cause for the acceleration. This outgassing received combined engineering and scientific attention because it has potential implications both for spacecraft navigation performance and for contamination of the collected samples. Thermal modeling, laboratory studies of SRC materials, and monitoring of the acceleration are all consistent with H2 O as the main component of the outgassing. Dedicated, in-flight campaigns continued to expose the SRC to sunlight until the acceleration dropped to the acceleration noise floor. Any residual amounts of H2 O outgassing are not considered to be a hazard with regards to mission operations or pristine sample acquisition. The sample stow procedure has been updated to ensure that no direct line of site exists between any residual outgassing and the samples during future operations. Similar outgassing of the Stardust SRC probably also occurred. No adverse contamination of Stardust samples was observed that could be associated with this process. Future missions that use similar reentry vehicles should consider procedures to test for and, if necessary, mediate such outgassing after launch. Highlights: OSIRIS-REx accelerated slightly when sunlight hit its sample return capsule (SRC). Outgassing from the SRC is the most likely cause of the acceleration. Thermal modeling, lab studies, and spacecraft monitoring are all consistent with H2 O outgassing. Outgassing of remaining H2 O is not a hazard to mission operations or pristine sample acquisition. Similar outgassing of the Stardust SRC probably also occurred.